Edible Antimicrobial Films Based on Microencapsulated Lemongrass Oil - Bustos-Cerda, R; Matiacevich, S (Springer India, 2016)
Edible films and coatings have been proposed as viable alternatives for the preservation of fresh food such as fruit, meat, fish and cheese. They can be designed to contain natural antioxidants, vitamins and antimicrobials in order to extend shelf life of the product keeping the natural sensorial properties. Essential oils have been targeted as potential active principles for edible films and coatings given their well-recognized antioxidant, antimicrobial and sensory properties. In the present work, lemongrass oil (LMO) microcapsules were prepared by the emulsification-separation method using sodium caseinate as wall material. Microcapsules had an average size of 22 μm and contained over 51 % oil in their nucleus. The release kinetics of the LMO components was studied for both, microcapsules and microcapsule containing films. Experimental data for the controlled release of LMO components showed good correlation with Peppas and Weibull models. The effect of the alginate matrix on the release parameters of the mathematical models could be detected by the modification of the b constant of the Weibull equation which changed from 0.167 for the microcapsules to 0.351 for the films. Films containing LMO at concentrations of 1250, 2500 and 5000 ppm were able to inhibit growth of Escherichia coli ATCC 25922 and Listeria monocytogenes ISP 65–08 in liquid cultures. A possible future application of these films for shelf life extension of fresh food is discussed. © 2015, Association of Food Scientists & Technologists (India).